The role of green IT and IT for green within green supply Chain management: A preliminary finding from ISO14001 companies in Malaysia - Savita, K.S. (Springer Verlag, 2015)
The purpose of this study is to investigate the role of Information Technology and Information System for Environmental Sustainability in Green Supply Chain Management within the context of manufacturing firms in Malaysia. More specifically, the pilot findings reveal that Green IS related activities among manufacturing firms in Malaysia are present, but measuring the extent of overall effectiveness of Green IS practices is not being carried out adequately. The data collection instrument used for the pilot study was distributed to the management team of 50 organizations and only 32 responses were received. With a response rate of 64 for the pilot study, the results of the preliminary analysis indicates that manufacturing organizations in Malaysia are practicing green in Malaysia, but have yet to track and audit the exact energy efficiency level. Â© Springer International Publishing Switzerland 2015.